Damage Control in Trauma Care An Evolving Comprehensive Team Approach (Springer International Publishing, 2018)
This book describes current, evidence-based guidelines for damage control interventions across the field of trauma care with the aim of enabling clinicians to apply them to best effect in daily clinical practice. Emphasis is placed on the need for trauma surgeons and their teams to recognize that optimal damage control in severely traumatized patients depends upon the combination of immediate assessment, resuscitation, and correct surgical management. The book opens by examining the evolution of damage control and the very significant impact that military damage control interventions have had on civilian emergency health care through improvements as simple as bandaging and tourniquets. Damage control measures in different specialties, including neurosurgery, orthopedics, vascular surgery, cardiothoracic surgery, anesthesia, and critical care, are then covered in detail. Readers will also find helpful information on a range of other important topics, such as the role of pre-hospital care providers, damage control within the emergency department, adjuncts of damage control, and damage control in austere environments. This book is a 'must read' for all clinicians in the trauma field.